Culture for Health Promotion and Improvement of Health Outcome in Southeastern Nigeria: A Comparative Analysis of Kola Nut (Oji), Bitter Kola (Akilu), African Pepper Fruit (Mmimi), and Alligator Pepper as Lens - Ahajumobi, N. E. (European Journal of Applied Sciences, 2026)
Background: All over the world culture shapes how we perceive pain, what humans describe as good or “good life”, and how people ask for help. Culture is a binder, which influences a person’s health behaviours and psychological resilience. Effective health services are often rejected, where such failed to acknowledge, and respect people’s culture. Objectives: A comparative analysis to determine how cultural or traditional nutraceutical foods such as, Kola nut (Oji), BitterKola (Akilu), African Pepper fruit (Mmimi), and Alligator pepper (Oso oji) could create a road map and pave way for green economy, easy acceptance and use of cultural foods, which evidence has shown to possess potency for health restoration to ensure that findings bring about the desired social change. Theory: Systematic- Comparative Review: Community approach to intervention services. Methods: Searched the Internet, google scholar for data mining, and examined data to learn from the existing evidence about the nutritional, chemical, and phytochemical composition of. Only peer reviewed data obtainable from the internet were included, other sources were excluded. Results: Evidence showed that the aforementioned cultural food are high in macro and micronutrients, as well as phytochemical compounds, which evidence linked with pharmacological properties. Conclusion: Kola nut, Bitter Kola, African Pepper fruit, and Alligator pepper are rich in nutraceutical and being traditional revered food pave way for evidence easy acceptance and use for food and healing remedies.